Influence of Weight Bearing on Postoperative Complications after Surgical Treatment of the Lower Extremity - Eickhoff, Alexander Maximilian; Cintean, Raffael; Fiedler, Carina; Gebhard, Florian; Schütze, Konrad; Richter, Peter (Zeitschrift für Orthopädie und Unfallchirurgie, 2022)
Purpose In order to prevent implant failure and secondary fracture dislocation, it is often recommended that patients perform partial weight-bearing after surgery of the lower extremity. Previous examinations showed that patients are often not able to follow these instructions. In this study, patients who had undergone surgery of the lower extremity were studied in order to analyze whether incorrect loading influenced the number and severity of complications.Methods Fifty-one patients were equipped with electronic shoe insoles, which measure loading and other parameters. The measurement period was 24 to 102 hours. Median duration of follow-up was 490 days. The primary outcome parameter was postoperative complications leading to revision surgery. Statistical analysis was performed using the chi-square and Fisher exact tests with significance set at a p < 0.05.Results Seven out of fifty-one patients had postoperative complications. Four wound complications, one implant failure, chronic instability after fracture of the tibia, and one implant loosening of a hip prosthesis were recorded. In total, 26 of 39 patients were not able to follow the postoperative instructions. Five of the twenty-six patients with difficulties in partial weight-bearing suffered a postoperative complication. In comparison, only 2 of the other 25 patients were affected. There was no statistically significant correlation between high weight-bearing and occurrence of complications (p = 0.29).Conclusion Most of the patients were unable to follow the surgeon’s instructions for partial weight-bearing. Excessive loading did not seem to influence the number and severity of postoperative complications, especially regarding implant failure. Therefore, we should continue with measurements and reevaluate the “partial weight-bearing doctrine”.
Keywords: Teilbelastung; Belastung; Komplikationen; elektronische Schuheinlagen